Comparative evaluation of Rock- Eval and elemental analysis to determine organic carbon content in sediment samples - Pyliotis, I.; Hamilaki, E.; Pasadakis, N.; Manoutsoglou, E. (Bulletin of the Geological Society of Greece, 2013)
Rock-Eval and Elemental Analysis techniques are widely used in Organic Geochemistry for the determination of the organic content in sediment samples. Both techniques determine the carbon content using thermal treatment and pyrolysis and/or oxidation reactions. Due to the complex nature of the geochemical samples (different mineralogical composition, low organic carbon content, e.t.c) and the differences of their operational principles, disagreements are commonly observed between the analytical results of these techniques. In this work we studied in a systematic manner the performance of both techniques on a common sample set, consisting of immature, poor in organic carbon, sediments. It was demonstrated that both techniques applied on original and acid-treated samples, provide consistent analytical results for carbon content; that has also been showed by its mass-balance calculations showed.